(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the current challenges and future prospects of operational audits in Uzbekistan’s banking sector within the context of the digital economy. As digital technologies reshape industries worldwide, the banking sector in Uzbekistan is leveraging these innovations to enhance service delivery, operational efficiency, and customer satisfaction. However, these advancements also introduce new complexities for operational audits. The study explores issues such as off-balance sheet transactions, audit quality, and outdated regulatory frameworks, comparing them with experiences in Russia and Belarus. The impact of digitalization, including the benefits and challenges of using data analytics, artificial intelligence, and blockchain in audits, is also analyzed. The article concludes with recommendations for enhancing auditor expertise, implementing advanced technologies, and updating regulatory frameworks to ensure effective and reliable operational audits in Uzbekistan’s digital economy.